Civil war and U.S. foreign intervention - Albornoz, Facundo; Hauk, Esther (Elsevier, 2014)
We study how foreign interventions affect civil war around the world. In an infinitely repeated game we combine a gambling for resurrection mechanism for the influencing country with the canonical bargaining model of war in the influenced country to micro-found sudden shifts in power among the domestic bargaining partners, which are known to lead to war due to commitment problems. We test two of our model predictions that allow us to identify the influence of foreign intervention on civil war incidence: (i) civil wars around the world are more likely under Republican governments and (ii) the probability of civil wars decreases with the U.S. presidential approval rates. These results withstand several robustness checks and, overall, suggest that foreign influence is a sizable driver of domestic conflict.